Implementasi manajemen risiko dalam pengelolaan mobile banking pada perbankan syariah - Wijayanti, U’ut (Maliki Interdisciplinary Journal, 2024)
The Islamic financial sector has been established and growing in Indonesia for more than ten years. The Fourth Industrial Revolution (4.0) and supported by the covid-19 pandemic has brought a new era of globalisation and information technology revolution, which has expanded the reach of financial institutions and made them more sophisticated, competitive and dynamic than ever. The development of technology-based banking products includes Autometicly Teller Machine (ATM), Electronic Data Capture (EDC), Mobile Banking, E-Money and Internet Banking. While there are benefits of digital banking for the banking sector, there is also the possibility that irresponsible parties will carry out threats to the system. Banks also need to pay attention to protecting the security of their customers along with the development of digital banking. Islamic banks must have the ability to adapt to the environment in this digital era while still implementing risk management in accordance with sharia principles. Based on the above phenomenon, it is interesting to conduct a deeper analysis of the implementation of risk management aspects of mobile banking services in Islamic banking. This research uses a literature study method that can be used to answer research problems using descriptive analysis techniques. The data used for this research is secondary data sourced from books, journals, websites, and other materials related to the research topic of mobile banking risk management.